2020
DOI: 10.3390/insects11040254
|View full text |Cite
|
Sign up to set email alerts
|

Differential Foraging of Indigenous and Exotic Honeybee (Apis mellifera L.) Races on Nectar-Rich Flow in a Subtropical Ecosystem

Abstract: In the subtropics, agricultural activities such as beekeeping are greatly influenced by environmental challenges. In the desert of Central Arabia, honeybees forage on limited prairies that are affected by adverse weather conditions. Bee colonies reduce their field activities during extremely hot-dry-windy weather. This study investigated whether nectar-rich melliferous flora enhance the field activities of two honeybee subspecies, Apis mellifera jemenitica (indigenous) and A. m. carnica (exotic), despite the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
2
0
2
Order By: Relevance
“…Of these upregulated DEGs, there were 15 HSPs, including HSP40, HSP70, HSP90, L (2) efl, and so on (Supplementary Figure 2). HSPs, as highly conserved molecular chaperones, can influence the folding and functional conformation of proteins (Purschke et al, 2017;Alqarni, 2020). Both GO and KEGG enrichment analysis were associated with the protein processes, which confirmed that heat stress could induce a rapid response by the organism to synthesize resistance proteins and protect against damage (Scheffer et al, 2022).…”
Section: Discussionmentioning
confidence: 74%
“…Of these upregulated DEGs, there were 15 HSPs, including HSP40, HSP70, HSP90, L (2) efl, and so on (Supplementary Figure 2). HSPs, as highly conserved molecular chaperones, can influence the folding and functional conformation of proteins (Purschke et al, 2017;Alqarni, 2020). Both GO and KEGG enrichment analysis were associated with the protein processes, which confirmed that heat stress could induce a rapid response by the organism to synthesize resistance proteins and protect against damage (Scheffer et al, 2022).…”
Section: Discussionmentioning
confidence: 74%
“…This stress not only affects pollination services, foraging behavior, and the overall growth of pollinators but also triggers observable changes in these areas (Zhao et al, 2021). These negative effects are projected to be even more pronounced as climate change progresses, with significant shifts expected in tropical, cold, and mountainous regions, as previously noted by Medina et al (2018), Alqarni (2020), andSoroye et al (2020). The primary driving force behind these changes is the heightened frequency and duration of heat waves, which have become a prominent characteristic of climate change (Xu et al, 2018).…”
Section: Pollination and Floweringmentioning
confidence: 80%
“…The current results showed that rape, date palm and the Acacia trees are the main pollen sources in the harshest environmental region of Saudi Arabia (Riyadh). In the same area Alqarni (2020), recorded notable foraging behaviour for the A. m. jemenitica (indigenous) and A. m. carnica (exotic) on the Acacia trees (Acacia gerrardii Benth.). In eastern province of Saudi Arabia in Al-hasa region (semi-arid), Al-Jabr and Nour (2001), stated that rape, date palm and the Acacia trees considered main pollen sources for honey bees.…”
Section: Pollen Botanical Sources and Flowering Periodsmentioning
confidence: 95%